Comparative visual function in four piscivorous fishes inhabiting Chesapeake Bay - Horodysky, Andrij Z; Brill, Richard W; Warrant, Eric J; Musick, John A; Latour, Robert J (Journal of experimental biology, 2010)
Maintaining optimal visual performance is a difficult task in photodynamic coastal and estuarine waters because of the unavoidable tradeoffs between luminous sensitivity and spatial and temporal resolution, yet the visual systems of coastal piscivores remain understudied despite differences in their ecomorphology and microhabitat use. We therefore used electroretinographic techniques to describe the light sensitivities, temporal properties and spectral sensitivities of the visual systems of four piscivorous fishes common to coastal and estuarine waters of the western North Atlantic: striped bass (Morone saxatilis), bluefish (Pomatomus saltatrix), summer flounder (Paralichthys dentatus) and cobia (Rachycentron canadum). Benthic summer flounder exhibited higher luminous sensitivity and broader dynamic range than the three pelagic foragers. The former were at the more sensitive end of an emerging continuum for coastal fishes. By contrast, pelagic species were comparatively less sensitive, but showed larger day-night differences, consistent with their use of diel light-variant photic habitats. Flicker fusion frequency experiments revealed significant interspecific differences at maximum intensities that correlated with lifestyle and habitat. Spectral responses of most species spanned 400-610 nm, with significant day-night differences in striped bass and bluefish. Anadromous striped bass additionally responded to longer wavelengths, similar to many freshwater fishes. Collectively, these results suggest that pelagic piscivores are well adapted to bright photoclimates, which may be at odds with the modern state of eutrified coastal and estuarine waters that they utilize. Recent anthropogenic degradation of water quality in coastal environments, at a pace faster than the evolution of visual systems, may impede visually foraging piscivores, change selected prey, and eventually restructure ecosystems.